Antibiotic Resistance in Cases of Bacterial Meningitis: Literature Review - Warihan Unok; Ratna Devi; Fanindya Hadamu; M. Sabir Mangawing; Ary Anggara (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Meningitis is an infectious disease that attacks the cerebral membrane or swallows. Meningite is among the ten most dangerous diseases in the world. The disease can affect both children and adults. The cause of this disease can be bacteria, viruses, fungi, or aseptic. Most cases of viral meningitis usually heal themselves and are not fatal, but in severe cases, such as bacterial, biased, life-threatening. Methods: Articles related to bacterial meningitis taken from databases like Google Scholar, Pubmed and Portal Garuda over the last 5 years (2020- 2024). Use keywords: